PeERF1, a SHINE-Like Transcription Factor, Is Involved in Nanoridge Development on Lip Epidermis of Phalaenopsis Flowers - Lai, Pei-Han; Huang, Li-Min; Pan, Zhao-Jun; Jane, Wann-Neng; Chung, Mei-Chu; Chen, Wen-Huei; Chen, Hong-Hwa (Frontiers in Plant Science, 2020)
Phalaenopsis orchids have a spectacular floral morphology with a highly evolved lip that offers a landing platform for pollinators. The typical morphological orchid lip features are essential for the special pollination mechanism of Phalaenopsis flowers. Previously, we found that in the lip, a member of the AP2/EREBP protein family was highly expressed. Here, we further confirmed its high expression and characterized its function during lip development. Phylogenetic analysis showed that AP2/EREBP belongs to the Va2 subgroup of ERF transcription factors. We named it PeERF1. We found that PeERF1 was only expressed at stage 5, as flowers opened. This coincided with both thickening of the cuticle and development of nanoridges. We performed knockdown expression of PeERF1 using CymMV-based virus-induced gene silencing in either the AP2 conserved domain, producing PeERF1_AP2-silenced plants, or the SHN specific domain, producing PeERF1_SHN-silenced plants. Using cryo-SEM, we found that the number of nanoridges was reduced only in the PeERF1_AP2-silenced group. This change was found on both the abaxial and adaxial surfaces of the central lip lobe. Expression of PeERF1 was reduced significantly in PeERF1_AP2-silenced plants. In cutin biosynthesis genes, expression of both PeCYP86A2 and PeDCR was significantly decreased in both groups. The expression of PeCYP77A4 was reduced significantly only in the PeERF1_AP2-silenced plants. Although PeGPAT expression was reduced in both silenced plants, but to a lesser degree. The expression of PeERF1 was significantly reduced in the petal-like lip of a big-lip variant. PeCYP77A4 and PeGPAT in the lip were also reduced, but PeDCR was not. Furthermore, heterologous overexpression of PeERF1 in the genus Arabidopsis produced leaves that were shiny on the adaxial surface. Taken together, our results show that in Phalaenopsis orchids PeERF1 plays an important role in formation of nanoridges during lip epidermis development.